Repeating periodic eruptions of the supernova impostor SN 2000ch. Issue 2 (28th February 2023) - Aghakhanloo, Mojgan; Smith, Nathan; Milne, Peter; Andrews, Jennifer E; Filippenko, Alexei V; Jencson, Jacob E; Sand, David J; Van Dyk, Schuyler D; Wyatt, Samuel; Zheng, WeiKang
ABSTRACT: We analyse photometric observations of the supernova (SN) impostor SN 2000ch in NGC 3432 covering the time since its discovery. This source was previously observed to have four outbursts in 2000–2010. Observations now reveal at least three additional outbursts in 2004–2007, and 16 outbursts in 2010–2022. Outburst light curves are irregular and multipeaked, exhibiting a wide variety of peak magnitude, duration, and shape. The outbursts after 2008 repeat with a period of 200.7 ± 2 d, while the outburst in 2000 seems to match with a shorter period. The next outburst should occur around January/February 2023. We propose that these periodic eruptions arise from violent interaction around times of periastron in an eccentric binary system, similar to the periastron encounters of η Carinae leading up to its Great Eruption, and resembling the erratic pre-SN eruptions of SN 2009ip. We attribute the irregularity of the eruptions to the interplay between the orbit and the variability of the luminous blue variable (LBV) primary star, wherein each successive periastron pass may have a different intensity or duration due to the changing radius and mass-loss rate of the LBV-like primary. Such outbursts may occasionally be weak or undetectable if the LBV is relatively quiescent at periastron but can be much more extreme when the LBV is active. The observed change in orbital period may be a consequence of mass lost in outbursts. Given the similarity to the progenitor of SN 2009ip, SN 2000ch deserves continued attention in the event it is headed for a stellar merger or an SN-like explosion.